The Effects of Gamma Irradiation on Growth Response of Rodent Tuber (Typhonium flagelliforme Lodd.) Mutant in In Vitro Culture - NESTI FRONIKA SIANIPAR; ARIANDANA WANTHO; . RUSTIKAWATI; WILMAR MAARISIT (Bogor Agricultural University, Indonesia, 2013)
Rodent tuber (Typhonium flagelliforme Lodd.) is an Indonesian native plant that potential as anticancer. Even though the potential use of bioactive compounds from T. flagelliforme is very high, its genetic variation in Indonesia is low. Gamma irradiation can be used to increase genetic variation. The objective of this research was to obtain the first generation mutants (M1) of T. flagelliforme resulting from gamma irradiation of normal mother plantlets with different plant height and number of shoots. T. flagelliforme was irradiated at the doses of 0, 10, 20, 30, 40, and 50 Gy. The percentage of plant death was then calculated to determine the Lethal Dose (LD) 50. T. flagelliforme was then re-irradiated at LD50 dose to obtain M1 mutant. The plant height and number of shoots variation was observed after eight weeks of culture. The analysis of T. flagelliforme radiosensitivity resulted in LD50 at 25 Gy. Observation at six weeks after irradiation showed significant differences between the normal mother plant, 20 Gy mutants, and 25 Gy mutants with an average plant height of 9.57, 3.41, and 2.43 cm respectively, and the average number of shoots produced was 7.85, 6.03, and 5.00 shoots respectively. Irradiation at 20 and 25 Gy produced 49 and 37 mutant plantlets. This research showed that gamma irradiation at LD50 dose could generate plant height and number of shoots variation of M1 mutant plantlets that are different from normal mother plantlets.